Evaluasi Keberhasilan Reaktivasi Sumur EVR-595 Melalui Metode Pemotongan Casing Berdasarkan Aspek Layout Lokasi dan Well Integrity di Pertamina EP Lapangan Sangasanga - Eva Rifayanti; Fatma Fatma; M Nur Mukmin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Well reactivation is an effort to restore production from wells that have ceased operation due to technical and operational constraints. EVR-595 Well at Pertamina EP Sangasanga Field faced difficulties in rig service mobilization because of limited well pad area. This study aims to evaluate the success of well reactivation through the casing cutting method based on well pad layout and well integrity aspects. A descriptive quantitative case study was conducted using layout, well profile, production, and NORSOK D-010 standard data. The results show that cutting the casing by 5.17 m increased the working area to 6,760 m², exceeding the minimum rig service requirement of 2,340–2,700 m². The well integrity evaluation indicated that the formation pressure of 164.975 psi remained below the allowable limit. After reactivation, fluid production increased from 385.44 to 389.97 BFPD, while oil production decreased due to higher water cut. The casing cutting method successfully supported the reactivation of EVR-595 Well.